Design Case: Character Design Workshop for SDH Kupang Highschool Students - Hananto, Brian Alvin; Melini, Ellis; Zulkarnain, Alfiansyah; Heryanto, Naldo Yanuar; Indrajaya, Ferdinand (Penerbit Fakultas Desain Universitas Pelita Harapan, 2024)
This paper is a design case for a character design workshop for Sekolah Dian Harapan Kupang students. The workshop was done offline on 27th October 2023 and was attended by 36 high school students. The workshop itself went well, with various adjustments along the way. Through this design case, the author concluded that designers and workshop instructors must be flexible when conducting a workshop, as many unpredicted factors can influence the workshop’s conduct.